Ulcerated Gastric Lipoma Presenting with Gastrointestinal Bleeding and Hypovolemic Shock. Issue 1 (17th January 2022) - Marques, Pedro; Santos, Alexandra; Germano, Ana
Teaching Point: Gastric lipomas are very rare and generally asymptomatic benign tumors; however, they can manifest as life-threatening complications, readily diagnosed by CT.